Digital marketing usage among small rural businesses in Malaysia: an exploratory factor analysis (EFA) - Mohamad, Mohd. Amin (Human Resource Management Academic Research Society, 2022)
The purpose of this study is to evaluate the elements of digital marketing usage among small rural businesses using the EFA procedure. Furthermore, this study has developed and validated instrument of digital marketing usage in the context of rural businesses in Malaysia. This study utilized cross sectional research design. Quantitative data was collected as feasibility study data from 30 rural businesses in the state of Melaka, Malaysia, using self-administered survey. This study has finalized the instrument to six items with one dimension. This study has discussed the procedure to run EFA analysis for Digital Marketing Usage construct and calculated the value for Cronbach’s Alpha. It is suggested that future studies to look into different context in examining Digital Marketing Usage construct such among technology based business and urban small business.